Dividend Policy : Dipengaruhi oleh Leverage, Likuiditas, Profitabilitas dan Ukuran Perusahaan pada Perusahaan Foods and Beverages yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017 - Nugroho, Tatas Ridho; Ilmiddaviq, Muhammad Bahril (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
Dividend policy is a policy in dividing profit of the company that can be with name and everything, but in it practices often encountered dividing or paying it by unseen. Dividing dividend in appropriate time intervals that is every half year or in a year. This study aims to know about the influence of Leverage, Liquidity, Profitability, and Size towards Dividend Policy. This study using a quantitative approach by using a multiple linear regression analysis methods. The population in this study is registered companies in the stock exchange of Indonesia, food, and beverages year 2013-2017 is the main focus of this study. The sample of this study is collected by purposive sampling method. The result of the coefficient determination test that 34,7% is showing the ability of independent variable determine dependent variable, temporary 65,3% determine by other variables. The simultan test showed that independent variable together influence dependent variable and the partial test showed how does leverage has a negative significant impact towards dividend policy, liquidity hasn’t a significant impact towards dividend policy, profitability has a positive impact towards dividend policy and size hasn’t a significant impact towards dividend policy.